Risk and uncertainty in dam safety - Hartford, Desmond N. D. (Thomas Telford, 2004)
Through the presentation of a systematic and integrated process, this volume helps the dam owner to evaluate the needs for dam safety improvement, select and prioritise remedial and corrective actions, and improve maintenance, operating and surveillance procedures.
Sponsored by the Dam Safety Interest Group under the auspices of CEA Technologies Incoporated of Montreal, Canada.
Keywords: Dam safety.; Risk assessment.; elektronické knihy; electronic books